Molecular and morphological evidences confirm the statuses of Ancistroides othonias (Hewitson, 1878) and the subspecies of A. nigrita (Latreille, [1824]), sensu Evans 1949 (Lepidoptera, Hesperiidae) - Xue, Guoxi; Qu, Peng; Li, Meng; Chiba, Hideyuki; Li, Wenwei (Zootaxa, 2022)
Based upon analyses of the COI gene sequences and morphological characters, Ancistroides othonias (Hewitson, 1878) is proved to be a separate species rather than a female form of A. armatus (H. Druce, 1873) or a subspecies of A. nigrita (Latreille, [1824]), and Tagiades maura Snellen, 1886 is confirmed as its junior synonym. A. fumatus (Mabille, 1876) is restored to a full species from a subspecies of A. nigrita. Genitalia of A. othonias, A. nigrita, A. fumatus, A. armatus and A. longicornis are illustrated and described. Some taxonomic notes and discussion are provided.